Giant intracardiac blood cyst: assessing the relationship between its formation and previous cardiac surgery - Halim, J. (Neth Heart J, 2015)
This case report discusses a 23-year-old male patient who presented with shortness of breath during exercise. Echocardiography revealed an intracardiac mass located on the mitral valve. His medical history included surgical closure of an atrial septal defect type 2 at the age of 2 years. After being discussed within a multidisciplinary heart team, the intracardiac mass was surgically removed. Histopathological examination revealed a blood cyst. This case report emphasises that the presence of an acquired intracardiac cyst is a rare entity and that a pathophysiological association between the formation of a blood cyst and previous cardiac surgery has not been proven yet. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s12471-015-0707-4) contains supplementary material, which is available to authorized users.